Volume 7B: Structures and Dynamics 2014
DOI: 10.1115/gt2014-25292
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Optimization of Thrust Bearings Operated With Lubricants of Spatially Varying Viscosity

Abstract: In the present work, a CFD-based optimization study of thrust bearings lubricated with spatially varying viscosity lubricants is presented, with the main goal of minimizing friction coefficient. In practice, spatial variation of viscosity could be achieved by utilizing electrorheological or magnetorheological fluids. The bearings are modeled as two-dimensional channels, consisting of a smooth moving wall (rotor), and a parallel or inclined stationary wall (stator), which can be (i) smooth, (ii) partially textu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The present work builds on top of recent research related to the effect of surface treatment methods on the tribological performance of hydrodynamically lubricated contacts. In particular, two different methods will be evaluated, those of hydrophobicity and artificial surface texturing, which have been applied in journal and thrust bearings giving substantial potential of performance improvement, as it can also be seen in Fatu et al, 13 Pavlioglou et al, 14 and Guo-Jun et al 15 and Etsion et al, 16 Papadopoulos et al, 17 and Xiong and Wang 18 respectively. Hydrophobic surfaces draw their origins from the lotus leaf, and, due to their particular nanostructure, they are wetting resistant, exhibiting low levels of friction during fluid flow.…”
Section: A Combined Numerical and Experimental Work On Piston Ring Frmentioning
confidence: 99%
See 1 more Smart Citation
“…The present work builds on top of recent research related to the effect of surface treatment methods on the tribological performance of hydrodynamically lubricated contacts. In particular, two different methods will be evaluated, those of hydrophobicity and artificial surface texturing, which have been applied in journal and thrust bearings giving substantial potential of performance improvement, as it can also be seen in Fatu et al, 13 Pavlioglou et al, 14 and Guo-Jun et al 15 and Etsion et al, 16 Papadopoulos et al, 17 and Xiong and Wang 18 respectively. Hydrophobic surfaces draw their origins from the lotus leaf, and, due to their particular nanostructure, they are wetting resistant, exhibiting low levels of friction during fluid flow.…”
Section: A Combined Numerical and Experimental Work On Piston Ring Frmentioning
confidence: 99%
“…Hydrophobic surfaces draw their origins from the lotus leaf, and, due to their particular nanostructure, they are wetting resistant, exhibiting low levels of friction during fluid flow. In order to modify Reynolds equation so as to account for hydrophobic surfaces, the no-slip boundary condition on the fluid-wall interface should be replaced with proper slip boundary conditions, see Fatu et al 13 and Guo-Jun et al 15 Instead of using Reynolds equation, Computational Fluid Mechanics (CFD) simulations can also be used, like in Pavlioglou et al, 14 and it has been confirmed that the corresponding results match sufficiently.…”
Section: A Combined Numerical and Experimental Work On Piston Ring Frmentioning
confidence: 99%